Penggunaan Short Message Service Ibu Nifas Terhadap Minat Kontrasepsi Jangka Panjang (MKJP) di BPM Siti Zubaidah Kenteng Nogotirto Gamping Sleman Yogyakarta - Wiwin Hindriyawati; Sri Maryanti (STIKes Karsa Husada Garut, 2016)
Technology Short Message Service (SMS) developed at this time. SMS into a technology that is inseparable from our daily lives1). Utilization in health services will be a need and become eligible to do. Data BKKBN DIY in January to August 2015 stating that all EFA actively KB 432 386 couples, who recorded IUD users is 105 882 (24.47%), implant 29 297 (6.7%)2). Data postpartum mother in BPM Siti Zubaidah 2014 3 months 40 puerperal women, in one year more than 150, but not comparable to the use of contraceptives LTM in one year there are two acceptors LTM. To determine the effect of the use of short message service postpartum mother to the interest of long-term contraception. Methods using a quasi-experimental (control group pretest-posttest). The research subjects are grouped into two which received different treatment. Each group received pretest (T1) and posttest (T2) to the questionnaire instrument. And given questionnaire at the time after being given treatment. Results analysis Spearman rho p: 0.000, and the coefficient of determination r: 0.9442, r2: 0. 891 (89.1%) due to increased interest in SMS, 10.9% were due to other factors. T test paired t test P: 0033. Conclusion the use of SMS has the effect of increasing interest in long-term contraception.